Detection and Predictors of Arrhythmia in Patients with Chronic Noncardioembolic Ischemic Stroke on Wearable Electrocardiogram Device - Akimoto, Yu; Ito, Yoshiro; Tsurushima, Hideo; Hosoo, Hisayuki; Marushima, Aiki; Hayakawa, Mikito; Nakamura, Kazuhiro; Fujita, Keishi; Terakado, Toshitsugu; Yamagami, Hiroshi; Matsumaru, Yuji; Ishikawa, Eiichi (Asian Journal of Neurosurgery, 2025)
The screening examination for arrhythmias in patients with chronic noncardioembolic ischemic stroke is limited. This study aimed to investigate the prevalence of arrhythmia in patients with chronic noncardioembolic ischemic stroke using a stick-on wearable device.This was a prospective observational study conducted between July 2020 and February 2022 involving 176 patients with a history of noncardioembolic ischemic stroke. Patients receiving anticoagulant therapy were excluded. For the evaluation of arrhythmias, the patients wore a stick-on wearable device for a maximum of approximately 7 days. We investigated the prevalence of arrhythmia and its associated factors.The mean measurement time was 121.3 ± 45.3 hours. Atrial fibrillation was present in 2 (1.1%) patients, frequent premature atrial contractions (PACs) in 69 (39.2%), and frequent premature ventricular contractions (PVCs) in 36 (20.5%). Regression analysis showed that the risk factors independently associated with frequent PACs were age (odds ratio [OR] 1.103, 95% confidence interval [CI] 1.055–1.153; p < 0.001) and cilostazol use (OR 2.681, 95% CI 1.338–5.371; p = 0.005). Regression analysis showed that the risk factors independently associated with frequent PVCs were age (OR 1.047, 95% CI 1.002–1.095; p = 0.043), male sex (OR 3.834, 95% CI 1.441–11.045; p = 0.013), and cilostazol use (OR 2.968, 95% CI 1.363–6.463; p = 0.006).The prevalence of frequent PVCs is higher in patients with chronic noncardioembolic ischemic stroke than in the general population. The stick-on wearable device is a useful screening tool for arrhythmia in patients with chronic noncardioembolic ischemic stroke.
Keywords: wearable device; noncardioembolic ischemic stroke; arrhythmia; atrial fibrillation; frequent premature atrial contractions; frequent premature ventricular contractions